Informal Institution on the Extension of Value Transformation: Experiences from Developing Countries - Rahman, Asif; Aaneela, Rufaida Shafiq (South Asian Journal of Social Sciences and Humanities, 2023)
The purpose of this study is to investigate the substantive impact of how informal institutions regulate and reciprocate the actions of formal institutions in order to determine the extent to which the value transformation of developing countries is maintained across traditional, modern, and post-modern ranges. Using concepts of Inglehart’s Evolutionary Modernization Theory and North’s Transaction Cost, we have attempted to develop a conceptual framework based on the collinearity, structure, and velocity of value transformation in order to identify subjective preferences for the conformance of the underlying culture and the bargaining nature of informal institutions within the institutional multiplicity. Comparing three developing regions (South Asia, Africa, and Latin America) has allowed us to identify prospective domains and rates for tracking these changes. As a result of this comparison, various socio-cultural scenarios of underlying cultures and political-economic scenarios of the bargaining nature of informal institutions surrounding the transition and sustainability of particular value propositions in developing nations have been found. These scenarios have been found to be influenced by historical path dependency and cultural change agents with varying impacts on informal institutions.